Formulation and physical quality evaluation of aromatherapy oil combining patchouli (Pogostemon cablin Benth.) and peppermint (Mentha piperita L.) essential oils - Wahyudi, Hendra; Hamzah, Hasyrul; Yudhawan, Indra (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2024)
Background: Indonesia is a major producer of essential oils, with patchouli and peppermint oils being widely used in aromatherapy. Aromatherapy products, such as wind oil, provide therapeutic benefits but are often underused by younger consumers. Developing formulations that appeal to a broader audience may increase their use. Objective: This study aimed to formulate an aromatherapy oil using patchouli and peppermint essential oils, evaluate its physical properties, and test consumer preferences. Method: Four formulations (F1–F4) were prepared with varying concentrations of patchouli and peppermint oils. Physical tests, including organoleptic, homogeneity, clarity, pH, and spreadability, were conducted over four weeks. A hedonic test with 20 respondents assessed sensory preferences. Results: Formulations remained stable in terms of homogeneity and clarity throughout the study. pH values were within the acceptable range for skin application, though they increased slightly during storage. Spreadability improved over time, with F2, F3, and F4 meeting the ideal range by the fourth week. F4, containing 6% patchouli and 15% peppermint oils, was the most preferred in the hedonic test, particularly for color, smell, and clarity. Conclusion: Patchouli and peppermint essential oils can be effectively combined to create a stable, consumer-preferred aromatherapy oil. F4 showed the best physical and sensory qualities, making it a promising formulation for future development.